2006
DOI: 10.2134/agronj2005.0313
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Planting Date, Clipping Height, and Cultivar on Forage and Grain Yield of Winter Wheat in Argentinean Pampas

Abstract: In Argentinean Pampas, new wheat (Triticum aestivum L.) cultivars are routinely introduced to farmers for dual-purpose production. The objective of this study was to evaluate the effect of planting date, clipping height on forage, and grain yield for wheat cultivars. Treatments were arranged as a 3 3 3 3 3 factorial distributed in a splitsplit plot within a randomized complete block design. Main plots were planting date (March, April, and May); split-plots were clipping height (3 cm, 7 cm, and no clipping); an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
45
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 24 publications
8
45
3
Order By: Relevance
“…Despite the 25% grain yield penalty from forage removal in dual-purpose systems, economic analysis revealed considerably higher revenue in this system. The greater feasibility of dual-purpose systems compared with grain-only systems has been noted (Arzadun et al, 2003(Arzadun et al, , 2006Decker et al, 2009). Arzadun et al (2006) evaluated the increase of beef weight versus the decrease of wheat grain yield at increasing grazing pressures in a dual-purpose system and concluded that increased grazing pressure (grazing height from 7 to 3 cm) was profitable for farmers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the 25% grain yield penalty from forage removal in dual-purpose systems, economic analysis revealed considerably higher revenue in this system. The greater feasibility of dual-purpose systems compared with grain-only systems has been noted (Arzadun et al, 2003(Arzadun et al, , 2006Decker et al, 2009). Arzadun et al (2006) evaluated the increase of beef weight versus the decrease of wheat grain yield at increasing grazing pressures in a dual-purpose system and concluded that increased grazing pressure (grazing height from 7 to 3 cm) was profitable for farmers.…”
Section: Discussionmentioning
confidence: 99%
“…The greater feasibility of dual-purpose systems compared with grain-only systems has been noted (Arzadun et al, 2003(Arzadun et al, , 2006Decker et al, 2009). Arzadun et al (2006) evaluated the increase of beef weight versus the decrease of wheat grain yield at increasing grazing pressures in a dual-purpose system and concluded that increased grazing pressure (grazing height from 7 to 3 cm) was profitable for farmers. Perhaps the adoption of an appropriate dual-purpose system simplifies crop-livestock integration in this region, which will have economic and ecological advantages, such as (i) implementation of a dual-purpose system can enhance a system's profitability, which is extremely important, especially in rural areas, and (ii) the successful use of dual-purpose systems contributes to environmental protection because it prevents Table 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Winter wheat breeding and research programs in the United States have traditionally targeted improved grain yield and quality for human consumption (Arzadún et al, 2006;Carver et al, 1991;Carver et al, 2001;Winter and Thompson, 1990). On the other hand, forage associated traits such as forage yield and nutritive value have not been major breeding goals in winter wheat breeding programs (Kim and Anderson, 2015).…”
mentioning
confidence: 99%
“…Its production is generally for grain purpose, while in countries such as Argentina, Australia, Morocco, Syria and Uruguay, wheat crop is cultivated for grain as well as for fodder purpose. Wheat is the major crop in term of area and production [1]. The pasture of wheat is of great value because of its quality and quantity compared to other crops in late fall, winter or early spring season [2].…”
Section: Introductionmentioning
confidence: 99%